Sodium-ion battery positive electrode material as well as preparation method and application thereof
By adjusting the ratio of sodium to phosphate, high-purity Na4+xFe3(PO4)2+y(P2O7) material is prepared, which solves the problem of low conductivity of the positive electrode material of sodium ion battery, improves capacity and rate performance, and is suitable for large-scale production .
Patent Information
- Application Number
- CN202411277496.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sodium ion battery cathode materials have affected the capacity and rate performance of the material due to their low electronic conductivity and ionic conductivity resistance, and cannot be commercially used.
By adjusting the ratio of sodium to phosphate, a high-purity and high crystallinity Na4+xFe3(PO4)2+y(P2O7) material was prepared, which increased the electron and ionic conductivity of the material and formed a fully activated iron-based polyanionic electrode. , optimize the diffusion structure of sodium ions.
It significantly improves the specific capacity and rate performance of the cathode material, is suitable for large-scale production applications, and does not require additional synthesis processes, which affects the existing manufacturing process small.
Smart Images

Figure CN119133443A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, clean energy such as wind power, tidal power, and solar energy have been vigorously promoted. However, due to their inherent intermittent and volatile characteristics, they are incompatible with the power grid, and there is an urgent need to use electrochemical energy storage systems to meet the demand. At present, lithium-ion battery technology is the most mature and almost dominates the electrochemical energy storage market. However, the uneven distribution of lithium resources around the world and the large fluctuations in the price of lithium carbonate have significantly increased the cost of lithium batteries. Therefore, the relatively low-priced sodium-ion batteries have become one of the main choices for large-scale energy storage and low-speed power.
[0003] There are many types of positive electrode materials for sodium-ion batteries, such as transition metal oxides, Prussian blue analogs, and polyanion compounds. Among them, transition metal oxides have complex phase changes, poor cycle stability, and the mechanism is not yet clear; Prussian blue analogs have serious problems with crystal water. Compared with the first two materials, polyanion compounds are stable, have moderate capacity, and are highly safe. Therefore, polyanion compounds are considered to be one of the most suitable positive electrode candidates for sodium-ion batteries, and have therefore received great attention in recent years. Compared with vanadium-based phosphates, iron-based phosphates have the advantages of low toxicity and low cost, which are more conducive to industrialization. Among iron-based phosphates, sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2(P2O7)) combines the advantages of iron-based phosphates: low cost, high theoretical capacity, high operating voltage, long cycle life, and environmental friendliness, and is considered to be the most promising positive electrode material for sodium-ion batteries. However, its inherent low electronic conductivity and ionic conductivity resistance seriously affect the capacity and rate performance of the material, and it cannot be commercially applied. Summary of the invention
[0004] In order to solve the problems existing in the background technology, the present invention provides a sodium ion battery positive electrode material and a preparation method and application thereof. The prepared sodium ion battery positive electrode material Na 4+x Fe3(PO4) 2+y (P2O7) has high purity, good crystallinity, high ionic and electronic conductivity, which greatly improves the specific capacity and rate performance of the positive electrode material. The preparation method of the positive electrode material for sodium ion batteries described in the present invention does not require additional synthesis processes, has little impact on the existing manufacturing process, is easy to control, and is suitable for large-scale production applications.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A sodium ion battery positive electrode material, the molecular formula of the sodium ion battery positive electrode material is Na 4+x Fe3(PO4)2+y (P2O7), where 0 <x<1.3,0<y<1.3,0<x / y<3。
[0007] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0008] The raw sodium source compound, iron source compound and phosphorus source compound are mixed evenly and then calcined in an inert atmosphere or a reducing atmosphere to prepare a sodium ion battery positive electrode material, wherein the stoichiometric ratio of the sodium source: iron source: phosphorus source is 4+x:3:4+y.
[0009] Furthermore, the calcination step is: keeping the raw material mixture at 200-400° C. for 3-8 hours, and then keeping it at 500-700° C. for 10-14 hours.
[0010] Further, the iron source compound includes one or a combination of iron powder, ferric citrate, ferrous citrate, ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous oxide, ferrous oxide, ferrous oxalate, ferrous oxalate, ferric acetate, ferric phosphate, ferric pyrophosphate, and ferrous sulfate.
[0011] Furthermore, the phosphorus source compound includes one or a combination of sodium dihydrogen phosphate, sodium phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, pyrophosphoric acid, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0012] Furthermore, the sodium source compound includes one or a combination of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0013] Furthermore, the method of mixing the raw materials includes ball milling, aqueous solution dissolution, or a combination of both.
[0014] Furthermore, the inert atmosphere is argon; and the reducing atmosphere is a mixed gas of hydrogen and argon.
[0015] Furthermore, the raw materials need to be fully dried, and the drying method includes one or a combination of air drying, vacuum drying, freeze drying, and spray drying.
[0016] An application of the sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material is used in a sodium ion battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention prepares a fully activated iron-based polyanion sodium ion battery positive electrode material, which can improve the energy density of the material. The iron-based polyanion electrode material with three-dimensional channels is easy to form an orderly arrangement structure of sodium ions / vacancies during the charging process because the oxygen atoms are fixed by phosphate and pyrophosphate, thereby affecting the further diffusion of sodium ions, and Na + The full filling of Na can effectively avoid the formation of an ordered arrangement of sodium ions / vacancies, making further diffusion of sodium ions possible, and the appropriate amount of Na + The introduction of increases the sodium removal amount of the material, and ultimately increases the capacity density of the material.
[0019] 2. The present invention only adjusts the ratio of sodium to phosphate to make the stoichiometric ratio of sodium to iron in the raw material greater than 4:3, thereby eliminating Na 4+x Fe3(PO4) 2+y (P2O7) NaFePO4 impurities and form a fully activated pure phase Na 4+x Fe3(PO4) 2+y (P2O7), improve the crystallinity of the material; the preparation method is simple and controllable, does not require additional synthesis process, and has little impact on the existing manufacturing process. 4+x Fe3(PO4) 2+y (P2O7) has high purity, good crystallinity, high ionic and electronic conductivity, and is suitable for large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD diagram of the sodium ion battery positive electrode material prepared in Comparative Example 1 and Examples 1-5;
[0021] Figure 2 The charge and discharge curves of the sodium ion battery positive electrode material assembled battery prepared in Comparative Example 1 and Examples 1-5;
[0022] Figure 3 It is a rate performance diagram of the sodium ion battery positive electrode material assembled battery prepared in Comparative Example 1 and Examples 1-5. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Comparative Example 1
[0025] Synthesis and Performance Test of Na4Fe3(PO4)2(P2O7)
[0026] Triammonium phosphate, sodium citrate and ferrous oxalate were mixed in a molar ratio of 4:4:3, and the mixture was placed in an alumina-lined grinding jar filled with zirconium balls of different sizes. The ball mill was run on a ball mill for 12 hours. The ball milled product was vacuum dried and transferred to a tubular furnace controlled by argon atmosphere. It was heated to 250°C at a heating rate of 5°C / min and maintained at a constant temperature for 3 hours. Then it was heated to 700°C at the same rate and maintained at a constant temperature for 14 hours to obtain Na4Fe3(PO4)2(P2O7) material.
[0027] Figure 1 The X-ray diffraction characterization results prove that the sample prepared in this comparative example is mainly composed of Na4Fe3(PO4)2(P2O7) crystalline compound.
[0028] Na4Fe3(PO4)2(P2O7), SupperP, and PVDF were weighed and mixed in a mass ratio of 7:2:1, coated on an aluminum foil with a diameter of 19 mm, and then the aluminum foil was vacuum dried at 120°C for 10 hours to obtain a positive electrode. Sodium metal was used as the counter electrode, 1 mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) was used as the electrolyte, and the separator was cellgard2035. The button battery was assembled in a glove box. The battery model was CR2016.
[0029] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, in the voltage range of 1.7-4.0 V, the reversible specific capacity is 50 mA h g -1 The battery after charge and discharge is tested at a rate. The results are as follows: Figure 3 As shown, it was found that the rate performance of Na4Fe3(PO4)2(P2O7) electrode was poor.
[0030] Example 1
[0031] This embodiment provides a Na 4.3 Fe3(PO4) 2.3The preparation method of (P2O7) sodium ion positive electrode material comprises the following steps: triammonium phosphate, sodium citrate and ferrous oxalate are mixed in a molar ratio of 4.3:4.3:3, the mixed material is placed in an alumina lined grinding jar equipped with zirconium balls of different sizes, ball milling is performed on a ball milling device for 12 hours, the obtained ball milling product is vacuum dried and then transferred to a tube furnace controlled by an argon atmosphere, heated to 250°C at a heating rate of 5°C / min, maintained at a constant temperature for heat treatment for 3 hours, and then heated to 700°C at the same rate, maintained at a constant temperature for heat treatment for 14 hours, to obtain Na 4.3 Fe3(PO4) 2.3 (P2O7) material.
[0032] Figure 1 The X-ray diffraction characterization results show that the sample prepared in this embodiment is Na 4.3 Fe3(PO4) 2.3 Materials mainly composed of (P2O7) crystalline compounds.
[0033] Weigh Na in a mass ratio of 7:2:1 4.3 Fe3(PO4) 2.3 (P2O7), SupperP, PVDF and mixed, coated on an aluminum foil with a diameter of 19mm, and then vacuum dried the aluminum foil at 120℃ for 10 hours to obtain a positive electrode. Sodium metal is used as the counter electrode, 1mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) is used as the electrolyte, and the separator is cellgard2035. The button battery is assembled in a glove box, and the battery model is CR2016.
[0034] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, the reversible specific capacity is 90 mA h g in the voltage range of 1.7-4.0 V. -1 Compared with Na4Fe3(PO4)2(P2O7) in Comparative Example 1, the discharge capacity is increased by 40 mA hg -1 . Figure 3 As shown in its rate performance curve, compared with the Na4Fe3(PO4)2(P2O7) obtained in Comparative Example 1, the rate performance of the material filled with a small amount of sodium is better than that prepared in Comparative Example 1.
[0035] Example 2
[0036] This embodiment provides a Na 4.6 Fe3(PO4) 2.6The preparation method of (P2O7) sodium ion positive electrode material comprises the following steps: triammonium phosphate, sodium citrate and ferrous oxalate are mixed in a molar ratio of 4.6:4.6:3, the mixed material is placed in an alumina lined grinding jar equipped with zirconium balls of different sizes, ball milling is performed on a ball milling device for 12 hours, the obtained ball milling product is vacuum dried and transferred to a tube furnace controlled by an argon atmosphere, heated to 250°C at a heating rate of 5°C / min, maintained at a constant temperature for heat treatment for 3 hours, and then heated to 700°C at the same rate, maintained at a constant temperature for heat treatment for 14 hours, to obtain Na 4.6 Fe3(PO4) 2.6 (P2O7) material.
[0037] Figure 1 The X-ray diffraction characterization results show that the sample prepared in this embodiment is Na 4.6 Fe3(PO4) 2.6 Materials mainly composed of (P2O7) crystalline compounds.
[0038] Weigh Na in a mass ratio of 7:2:1 4.6 Fe3(PO4) 2.6 (P2O7), SupperP, PVDF and mixed, coated on an aluminum foil with a diameter of 19mm, and then vacuum dried the aluminum foil at 120℃ for 10 hours to obtain a positive electrode. Sodium metal is used as the counter electrode, 1mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) is used as the electrolyte, and the separator is cellgard2035. The button battery is assembled in a glove box, and the battery model is CR2016.
[0039] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, in the voltage range of 1.7-4.0 V, the reversible specific capacity is 92 mA h g -1 Compared with Na4Fe3(PO4)2(P2O7) in Comparative Example 1, the discharge capacity increased by 42 mA hg -1 . Figure 3 As shown in its rate performance curve, compared with the Na4Fe3(PO4)2(P2O7) obtained in Comparative Example 1, the rate performance of the material filled with an appropriate amount of sodium is better than that prepared in Comparative Example 1.
[0040] Example 3
[0041] This embodiment provides a Na 5.2 Fe3(PO4) 3.2The preparation method of (P2O7) sodium ion positive electrode material comprises the following steps: mixing triammonium phosphate, sodium citrate and ferrous oxalate in a molar ratio of 5.2:5.2:3, placing the mixture into an alumina lined grinding jar equipped with zirconium balls of different sizes, ball milling on a ball mill for 12 hours, vacuum drying the obtained ball milling product and transferring it to a tube furnace controlled by an argon atmosphere, heating it to 250°C at a heating rate of 5°C / min, maintaining a constant temperature for heat treatment for 3 hours, and then heating it to 700°C at the same rate, maintaining a constant temperature for heat treatment for 14 hours, to obtain Na 5.2 Fe3(PO4) 3.2 (P2O7) material.
[0042] Figure 1 The X-ray diffraction characterization results show that the sample prepared in this embodiment is Na 5.2 Fe3(PO4) 3.2 Materials mainly composed of (P2O7) crystalline compounds.
[0043] Weigh Na in a mass ratio of 7:2:1 5.2 Fe3(PO4) 3.2 (P2O7), SupperP, PVDF and mixed, coated on an aluminum foil with a diameter of 19mm, and then vacuum dried the aluminum foil at 120℃ for 10 hours to obtain a positive electrode. Sodium metal is used as the counter electrode, 1mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) is used as the electrolyte, and the separator is cellgard2035. The button battery is assembled in a glove box, and the battery model is CR2016.
[0044] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, the reversible specific capacity is 85 mA h g in the voltage range of 1.7-4.0 V. -1 Compared with Na4Fe3(PO4)2(P2O7) in Comparative Example 1, the discharge capacity is increased by 35 mA hg -1 . Figure 3 As shown in its rate performance curve, compared with the Na4Fe3(PO4)2(P2O7) obtained in Comparative Example 1, the rate performance of the material filled with a large amount of sodium is better than that of the material prepared in Comparative Example 1.
[0045] Example 4
[0046] This embodiment provides a Na 4.6 Fe3(PO4) 2.6The preparation method of (P2O7) sodium ion positive electrode material comprises the following steps: mixing pyrophosphate, sodium citrate and iron oxide in a molar ratio of 4.6:4.6:3, placing the mixture in an alumina-lined grinding jar equipped with zirconium balls of different sizes, ball milling on a ball mill for 12 hours, transferring the obtained ball milling product to a tube furnace controlled by an argon atmosphere after freeze drying, heating to 350°C at a heating rate of 5°C / min, maintaining a constant temperature for heat treatment for 6 hours, and then heating to 600°C at the same rate, maintaining a constant temperature for heat treatment for 14 hours, to obtain Na 4.6 Fe3(PO4) 2.6 (P2O7) material.
[0047] Figure 1 The X-ray diffraction characterization results show that the sample prepared in this embodiment is Na 4.6 Fe3(PO4) 2.6 Materials mainly composed of (P2O7) crystalline compounds.
[0048] Weigh Na in a mass ratio of 7:2:1 4.6 Fe3(PO4) 2.6 (P2O7), SupperP, PVDF and mixed, coated on an aluminum foil with a diameter of 19mm, and then vacuum dried the aluminum foil at 120℃ for 10 hours to obtain a positive electrode. Sodium metal is used as the counter electrode, 1mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) is used as the electrolyte, and the separator is cellgard2035. The button battery is assembled in a glove box, and the battery model is CR2016.
[0049] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, in the voltage range of 1.7-4.0 V, the reversible specific capacity is 91.5 mA h g -1 Compared with Na4Fe3(PO4)2(P2O7) in Comparative Example 1, the discharge capacity increased by 41.5 mA hg -1 . Figure 3 As shown in its rate performance curve, compared with the Na4Fe3(PO4)2(P2O7) obtained in Comparative Example 1, the rate performance of the material filled with an appropriate amount of sodium is better than that prepared in Comparative Example 1.
[0050] Example 5
[0051] This embodiment provides a Na 4.3 Fe3(PO4) 2.3The preparation method of (P2O7) sodium ion positive electrode material comprises the following steps: pyrophosphoric acid, sodium acetate and ferrous nitrate are put into water in a molar ratio of 4.3:4.3:3 and mixed evenly; the mixed material is put into a spray dryer for spray drying; the dried product is transferred to a tube furnace controlled by a mixed atmosphere of argon and hydrogen; the mixture is heated to 250°C at a heating rate of 5°C / min, and the temperature is kept constant for heat treatment for 6 hours; the mixture is heated to 550°C at the same rate, and the temperature is kept constant for heat treatment for 14 hours to obtain Na 4.3 Fe3(PO4) 2.3 (P2O7) material.
[0052] Figure 1 The X-ray diffraction characterization results show that the sample prepared in this embodiment is Na 4.3 Fe3(PO4) 2.3 Materials mainly composed of (P2O7) crystalline compounds.
[0053] Weigh Na in a mass ratio of 7:2:1 4.3 Fe3(PO4) 2.3 (P2O7), SupperP, PVDF and mixed, coated on an aluminum foil with a diameter of 19mm, and then vacuum dried the aluminum foil at 120℃ for 10 hours to obtain a positive electrode. Sodium metal is used as the counter electrode, 1mol / L NaClO4 ethylene carbonate / diethyl carbonate (volume ratio 1:1), fluoroethylene carbonate (volume fraction 5%) is used as the electrolyte, and the separator is cellgard2035. The button battery is assembled in a glove box, and the battery model is CR2016.
[0054] The constant current charge and discharge test was carried out with a current density of 26 mA g -1 The test results are as follows: Figure 2 As shown in Figure 2, in the voltage range of 1.7-4.0 V, the reversible specific capacity is 89 mA h g -1 Compared with Na4Fe3(PO4)2(P2O7) in Comparative Example 1, the discharge capacity increased by 39 mA hg -1 . Figure 3 As shown in its rate performance curve, compared with the Na4Fe3(PO4)2(P2O7) obtained in Comparative Example 1, the rate performance of the material filled with a small amount of sodium is better than that prepared in Comparative Example 1.
[0055] The present invention forms a fully activated Na by adjusting the stoichiometric ratio of sodium to phosphate and filling a small amount of sodium ions. 4+x Fe3(PO4) 2+y(P2O7) pure phase structure, the positive electrode material does not need to add other metal elements and additional synthesis process, and has little impact on the existing manufacturing process. The increase in Na content improves the ion and electronic conductivity, thereby greatly improving the specific capacity and rate performance of the positive electrode material, which is suitable for large-scale production applications.
[0056] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The molecular formula of the sodium ion battery positive electrode material is Na 4+ x Fe3(PO4) 2+y (P2O7), where 0 <x<1.3,0<y<1.3,0<x / y<3。 2. A method for preparing the positive electrode material for a sodium ion battery according to claim 1, characterized in that: The following steps are involved: The raw sodium source compound, iron source compound and phosphorus source compound are mixed evenly and then calcined in an inert atmosphere or a reducing atmosphere to prepare a sodium ion battery positive electrode material, wherein the stoichiometric ratio of the sodium source: iron source: phosphorus source is 4+x:3:4+y.
3. The preparation method according to claim 2, characterized in that: The calcination steps are: keeping the raw material mixture at 200-400°C for 3-8 hours, and then keeping it at 500-700°C for 10-14 hours.
4. The preparation method according to claim 2, characterized in that: The iron source compound includes one or a combination of iron powder, ferric citrate, ferrous citrate, ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous tetroxide, ferrous oxide, ferrous oxalate, ferrous oxalate, ferrous acetate, ferric phosphate, ferric pyrophosphate, and ferrous sulfate.
5. The preparation method according to claim 2, characterized in that: The phosphorus source compound includes one or a combination of sodium dihydrogen phosphate, sodium phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, pyrophosphoric acid, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
6. The preparation method according to claim 2, characterized in that: The sodium source compound includes one or a combination of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
7. The preparation method according to claim 2, characterized in that: The method of mixing the raw materials includes ball milling, aqueous solution dissolution, or a combination of the two.
8. The preparation method according to claim 2, characterized in that: The inert atmosphere is argon; the reducing atmosphere is a mixed gas of hydrogen and argon.
9. The preparation method according to claim 2, characterized in that: The raw materials need to be fully dried, and the drying method includes one or a combination of air drying, vacuum drying, freeze drying, and spray drying.
10. An application of the sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium ion battery positive electrode material is used in a sodium ion battery.
Citation Information
Patent Citations
Na4Fe3-x(PO4)2P2O7 / C sodium ion battery positive electrode material as well as preparation method and application thereof
CN112768673A
Iron-based phosphate sodium ion battery positive electrode material and preparation method thereof
CN114883540A
Sodium-rich sodium ferric pyrophosphate positive electrode material, preparation method and application
CN116119642A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117239120A
Preparation method of high-performance sodium ion battery positive electrode material Na4Fe3 (PO4) 2P2O7
CN117585658A
